KONSEP PENGEMBANGAN DUSUN BARU MURMAS KECAMATAN GANGGA KABUPATEN LOMBOK UTARA SEBAGAI DUSUN EKOWISATA BERBASIS BUDAYA - Liza Hani Saroya Wardi; Baiq Siti Noer Azima; Eti Julianti; Habibah, Habibah; Firman A. Wahab; Dodik Sutikno; Wildan Hakim (Bajang Institute, 2024)
The aim of this research is to find the concept of developing Dusun Baru Murmas as a culture-based tourist hamlet by identifying the potential of the hamlet that can be processed or developed as well as finding solutions to existing problems in the hamlet so that the development of Dusun Baru Murmas as a tourist hamlet that continues to maintain its authenticity. local culture and prioritizing the utilization of local potential as a tourist attraction that differentiates Baru Murmas hamlet from other tourist hamlets. To achieve this goal, the method used is the PRA method with various analyzes in it, namely evaluation analysis in the form of root problem analysis, goal analysis, project alternative analysis with data collection carried out by means of interviews, observation, photo mapping. There is great hope that with the development of Baru Murmas hamlet as a tourist hamlet, it will be able to bring about changes both socially, economically and culturally in efforts to solve problems that exist in Baru Murmas hamlet, especially in efforts to improve the welfare of the local community, which so far has not been prosperous due to the lack of natural potential. managed well due to the low human resources of their community